Temperature effects of ballastless track and dynamic responses of vehicle-track coupling system on tunnel floor with high temperature. (April 2023) - Lou, Ping; Sun, Zhen; Su, Xing
Abstract: Temperature has a great implication for the structural behavior of the ballastless track, however, there are few studies on the temperature effect of ballastless track and the dynamic responses of vehicle-track coupling system (VTCS) on tunnel floor with high temperature. In this paper, the finite element model is established to investigate this problem. The correctness of the model is verified by the test platform for the temperature field of track slab. The temperature stresses and warp deformations of the ballastless track on tunnel floor with high temperature are investigated, and then the additional irregularities of rail induced by the high temperature are used to study the dynamic responses of the VTCS. The results show that the longitudinal temperature stress of the track bed slab is the largest, and the stress increases nonlinearly with the increase of temperature. The maximum vertical deformation of the rail is less than that of the track bed slab. With the increase of the temperature, the dynamic responses of VTCS enlarge nonlinearly and the running safety index of the vehicle deteriorates. The limit value with 50 ℃ of the temperature difference between the tunnel floor and the environment is recommended. This paper provides the theoretical support for the design, maintenance and repair of the ballastless track in the tunnel with high temperature.